Dampak Kinerja Yang Dimediasi Oleh Kepuasan Kerja: Pengaruh Remunerasi Dan Pengawasan - Joko Dwitanto; Nur Afifah; Mustaruddin Mustaruddin (Journal on Education, 2024)
This article aims to examine the effect of remuneration and supervision on performance mediated by job satisfaction among the State Civil Apparatus (ASN) at the State Catholic College of Religion in Pontianak. The research was conducted using a quantitative approach. The data collection technique used was the census technique. The number of respondents was 71 people. Data analysis was performed using SPSS with path analysis and Sobel test methods. The results of the analysis showed that: (1) remuneration and supervision, both simultaneously and partially, have a positive and significant effect on job satisfaction, (2) remuneration and job satisfaction, both simultaneously and partially, have a positive and significant effect on performance, while the supervision variable has a negative and significant effect on performance, (3) remuneration has an insignificant effect on performance mediated by employee job satisfaction, and (4) supervision has a positive and significant effect on performance mediated by job satisfaction.